Individualized antiplatelet therapy - Geisler, T.; Gawaz, M. (Hämostaseologie, 2009)
Safeguarding of antiplatelet drug efficacy represents a cornerstone for the optimal treatment of patients with symptomatic coronary artery disease requiring coronary interventions. This means a challenge to modern cardiology since there has been cumulative evidence, that response to common oral anti -platelet therapy is a highly variable phenomenon underlying various mechanisms. It is known, that particular risk groups exhibit a high residual platelet aggregability (RPA) despite conventional antiplatelet therapy. Additionally, a relevant association between high RPA and recurrent ischaemic events after PCI exists. Individualization of antiplatelet therapy by dose increase or alternative application of novel P2Y12-receptor antagonists might lead to improved cardiovascular outcome in patients with poor responsiveness to conventional antiplatelet therapy. Identification of risk patients who might benefit from tailored therapy by increased net benefit without excess of major bleedings means a challenge. Clinical risk scores might help in the process of risk stratification and therapeutic decision. Subsequently, literature on risk assessment for antiplatelet drug responsiveness and different strategies will be discussed to identify patients who might benefit from personalized antiplatelet strategies.
Keywords: Antiplatelet